P446Myocardial ischemic tolerance and expression of selected genes in spontaneously hypertensive rats adapted to chronic continuous hypoxia. (15th July 2014) - Kolar, D; Brabcova, I; Zurmanova, J; Mandikova, P; Zajickova, P; Kalous, M; Pravenec, M; Novakova, O; Kolar, F; Neckar, J
Abstract: Purpose: Spontaneously hypertensive rats (SHR) are more susceptible to acute myocardial ischemia/ reperfusion injury than normotensive Brown Norway (BN) strain. It has been shown that the adaptation to chronic hypoxia improves ischemic tolerance in normotensive rats and the cardioprotective phenotype can be related to mitochondrial metabolism and signalling. Here we aimed at investigating effects of continuous normobaric hypoxia (CNH) on myocardial ischemic tolerance of SHR and conplastic strain SHR-mtBN (with mitochondrial genome from BN). We also analyzed the expression levels of selected genes of energy metabolism, antioxidant systems and signalling pathways. Methods: Rats were kept 21 days at CNH (inspired O2 fraction 0.1). Myocardial infarct size was determined after 20 min of ischemia and 2 h of reperfusion in open-chest rats (tetrazolium staining). In a separate group of animals, the total mRNA was isolated from left ventricles and gene expression was assessed by RT-PCR. Results: CNH reduced infarct size from 71 ± 4% of the area at risk in normoxic SHR to 49 ± 6% in hypoxic SHR. As compared to SHR, CNH induced more pronounced infarct size-limiting effect in SHR-mtBN. In both strains, CNH increased the mRNA expression of monoaminooxidase and β1-adrenoceptor, and decreased the expression of mitochondrial creatine kinase, superoxide dismutase, thioredoxin 2, thioredoxin-reductase 2 and peroxiredoxin 5. However, the expression of catalase, peroxiredoxin 3, mitochondrial hexokinase 2 and hypoxia-inducible factor 1α was markedly elevated in hypoxic SHR-mtBN as compared to hypoxic SHR. Conclusions: We demonstrate that CNH protects SHR hearts against acute ischemia/reperfusion injury with a possible involvement of mitochondrial genes. This work was supported by the Czech Science Foundation grant No. 13-10267S